2006
DOI: 10.1002/bit.21062
|View full text |Cite
|
Sign up to set email alerts
|

GlycoVis: Visualizing glycan distribution in the protein N‐glycosylation pathway in mammalian cells

Abstract: Glycosylation has profound effects on the quality of recombinant proteins produced in mammalian cells. The biosynthetic pathways of N-linked glycans on glycoproteins involves a relatively small number of enzymes and nucleotide sugars. Many of these glycoconjugate enzymes can utilize multiple N-glycans as substrates, thus generating a large number of glycan intermediates, and making the biosynthetic pathway resemble a network with diverging and converging paths. The N-glycans on secreted glycoprotein molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 57 publications
(44 reference statements)
3
30
0
Order By: Relevance
“…The studies on sialyltransferases' enzymatic activity usually consider G2F or Galb1-4GlcNAc as substrates, and data comparing G1F isomers to G2F as acceptor substrates are missing. 54 Similarly, to our knowledge, G1FS1 has not been studied as acceptor substrate for the galactosyltransferases. 52,[55][56][57] Thus, there is no data in the literature indicating that the presence of a sialic acid on one branch would be an obstacle for galactosylation of the other branch.…”
Section: Discussionmentioning
confidence: 95%
“…The studies on sialyltransferases' enzymatic activity usually consider G2F or Galb1-4GlcNAc as substrates, and data comparing G1F isomers to G2F as acceptor substrates are missing. 54 Similarly, to our knowledge, G1FS1 has not been studied as acceptor substrate for the galactosyltransferases. 52,[55][56][57] Thus, there is no data in the literature indicating that the presence of a sialic acid on one branch would be an obstacle for galactosylation of the other branch.…”
Section: Discussionmentioning
confidence: 95%
“…A simplified numeric representation instead of a text-based representation of glycan structures can further advance the development of computer aided analysis tools to study such a complex network [27]. We have demonstrated that the current numeric format can be easily applied to constructing and visualizing networks of glycan interactions.…”
Section: Discussionmentioning
confidence: 95%
“…Figure 6 exhibits the resulting network, which is a highly branched structure. It should be noted that the current network is an approximation of the glycosylation pathway in CHO cells since the enzymatic requirements and restrictions [27] were not fully considered during the network construction.…”
Section: Constructing Glycosylation Networkmentioning
confidence: 99%
“…The program also traces all possible reaction paths leading to each glycan and identifies each pathway on the map. Use of the program is illustrated with MALDI-TOF data from permethylated glycans from IgG and tissue plasminogen activator (TPA) (Hossler et al, 2006).…”
Section: Analysis Of Carbohydrates and Glycoconjugatesmentioning
confidence: 99%